2010
DOI: 10.1007/s00381-010-1123-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of continuous morphine infusions following pediatric cranial surgery in a surgical ward setting

Abstract: These findings suggest that CMI is comparable to acetaminophen and codeine with respect to analgesia and serious side effects. We recommend the use of CMIs as an alternative when pain is poorly controlled in post-operative pediatric neurosurgical patients to prevent the potential adverse consequences of inadequate analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…Our study revealed that in both younger and older pediatric patients, morphine administration was the most effective regimen of PCIA or NCIA after neurosurgery. These results are consistent with those of Warren 22 who suggested continuous morphine infusions (CMI) had an analgesic effect comparable to that of acetaminophen and codeine; yet codeine phosphate alone is typically preferred as the standard treatment for pain after cranial surgery. The fentanyl and tramadol group had similar analgesic effects; echoing results by Alencar 23 in neonates.…”
Section: Discussionsupporting
confidence: 89%
“…Our study revealed that in both younger and older pediatric patients, morphine administration was the most effective regimen of PCIA or NCIA after neurosurgery. These results are consistent with those of Warren 22 who suggested continuous morphine infusions (CMI) had an analgesic effect comparable to that of acetaminophen and codeine; yet codeine phosphate alone is typically preferred as the standard treatment for pain after cranial surgery. The fentanyl and tramadol group had similar analgesic effects; echoing results by Alencar 23 in neonates.…”
Section: Discussionsupporting
confidence: 89%
“…Opioids are generally considered to be the most effective analgesics, but they also carry the greatest risk of adverse effects [33]. Recommendations to improve safety while using opioid analgesics include dosing them by ideal body weight instead of actual body weight, and using opioids such as oxycodone and hydrocodone that do not rely on metabolism to achieve their analgesic effect [17,34,35].…”
Section: What Opioid Analgesics Are Available For Pain Control For Pementioning
confidence: 99%
“…Pain control involves a continuous morphine infusion protocol that has been described in previous publications. 8,11…”
Section: Methodsmentioning
confidence: 99%